Antimyosin scintigraphy for detection of cardiac amyloidosis - Lekakis, J.; Dimopoulos, M.; Nanas, J.; Prassopoulos, V.; Agapitos, N.; Alexopoulos, G.; Palazis, L.; Kostamis, P.; Stamatelopoulos, S.; Moulopoulos, S. (American Journal of Cardiology, 1997)
The diagnostic value of antimyosin scanning in 7 patients with biopsy- proven cardiac amyloidosis was examined in this study. Antimyosin imaging was positive in all amyloid patients, with more intense uptake in patients with heart failure.